Real-world efficacy of sublingual immunotherapy with Japanese cedar pollen for cypress pollinosis - Aiko Oka, MD; Tamami Yamashita, MD; Kengo Kanai, MD; Atsushi Yuta, MD; Yukiko Ogawa, MD; Eriko Takahara, MD; Hideki Shiratsuchi, MD; Akihiko Terada, MD; Takatsugu Tsunoda, MD; Takeshi Masuda, MD; Satoru Masuno, MD; Kenichi Kanai, MD; et al. (Journal of Allergy and Clinical Immunology: Global)
Background: It remains unclear whether allergen immunotherapy with Japanese cedar pollen extract is effective for Japanese cypress pollinosis in real-world settings. Objective: We sought to investigate the Japan-wide prevalence of cypress pollinosis, the efficacy of cedar sublingual immunotherapy (SLIT) on cypress pollinosis, the role of serum-specific IgE levels in pollinosis, and patients’ interest in the development of cypress SLIT. Methods: A cross-sectional, multicenter study using self-administered questionnaires was conducted in regions of Japan where cedar and cypress pollen dispersals are prevalent. This study included patients aged 5 to 69 years who received cedar SLIT in 2023. Results: Of 2597 participants analyzed, 84.5% experienced pollinosis symptoms during the cypress season before receiving cedar SLIT. Among these patients, 40.2% felt that cedar SLIT was less effective during the cypress season than during the cedar season. The longer the patients received cedar SLIT, the greater the inefficacy perceived during the cypress versus the cedar season. In the symptomatic patients, serum IgE levels were significantly higher for cedar and cypress as compared with those observed in subjects without symptoms during the cypress season. No significant differences were reported in IgE levels for cedar and cypress between patients reporting either high or lower efficacy for the cedar SLIT during cypress season. Interest in cypress SLIT was seen in 78.4% of these patients. Conclusions: Although there is a bias based on regional distribution, cedar SLIT has induced a limited efficacy on cypress pollinosis in real-world settings, suggesting a need for the development of cypress SLIT.